STRATEGI PENGURANGAN SUBSIDI BBM SEKALIGUS PENINGKATAN PENDAPATAN DENGAN IMPLEMENTASI KENDARAAN LISTRIK YANG RAMAH LINGKUNGAN - Aldi, Firmansyah (Jurnal Pijar, 2025)
This research aims to analyze strategies for reducing fuel oil (BBM) subsidies as well as increasing income by implementing environmentally friendly electric vehicles in Indonesia. The research method used is a literature study of reputable articles and books. The research results show that there are strategies that the government can implement, including the implementation of fiscal incentives, infrastructure development, international cooperation, and public campaigns and education. Furthermore, the potential for increasing state income through the adoption of electric vehicles can also occur due to budget savings in the form of reducing fuel subsidies. However, there are challenges related to the implementation of electric vehicles, including limited charging infrastructure, high initial vehicle costs, limited human resources, lack of public awareness, and frequently changing regulations. The opportunity for this implementation is that Indonesia has abundant nickel reserves to implement electric vehicles. Therefore, it is recommended that the government improve charging infrastructure, provide fiscal incentives, and carry out campaigns to increase public awareness about the benefits of electric vehicles. By implementing the right strategy, Indonesia can reduce fuel subsidies, increase state income, and create a healthy environment. Keywords: Fuel Subsidies, State Revenue, Electric Vehicles, Public Policy